Agama dan Sosiologi: Analisis Bibliometrik pada Database Dimensions dalam Kurun Tahun 2013-2022 - Indana Zulfa (Gunung Djati Conference Series, 2023)
Religion and Sociology are two diffetent things, but both are related to each other, so it is necessary to have research on both of them, with the hope that this connection can lead humans to prosperity. The purpose of this study is to analyze several published articles with the keyword Religion and Sociology using bibliometric analysis techniques. With quantitative methods and bibliometric analysis, the authors try to display several tables containing several different categories. In the results and discussion, five categories were found, namely 1) Research Category for Research Field Purposes and Sustainable Development Goals, 2) Annual Development, 3) Most Active Researcher, 4) Most Affiliates, and 5) Most Productive Publishing Locations. The conclusion of this study is that there is still a lack of interest from researchers in Indonesia in researching the study of Religion and Sociology. Even though in the category of affiliation and the most active publishing locations there are names from Indonesia, it still needs to be improved from the category of the most prolific writers.